La pluralidad religiosa del mundo en el siglo XV a través de la carta náutica de Mecia de Viladestes (1413)* - Sáenz-López Pérez, Sandra (Anales de Historia del Arte, 2012)
This article focuses on the nautical chart of 1413 by the Majorcan Mecia de Viladestes in order to show, through the analysis of its texts and images, the different religions which coexisted in the world of the fifteenth century, and how they were understood in the West. On this map there is space allocated for Christianity, Islam and the Indian religions; the personal experiences of the cartographer, a Jewish convert to Christianity in 1391, seem also to be revealed. Among the iconographic motifs that will be analyzed are the Red Sea which was crossed by the people of Israel and Mountain Sinai, where Moses received the Tablets of the Covenant; the city of Jerusalem and the Holy Sepulcher; the hajj or Muslim pilgrimage to Mecca; and the worshipping of the “idol of metal with nine heads and nine hands”.
Keywords: Mecia de Viladestes; nautical chart; Christianity; Islam; Judaism; Indian religion; mappamundi; pilgrimage; Mecca; idol.